Pengaruh Literasi Keuangan Islam terhadap Keputusan Investasi Generasi Milenial - Muhammad Al Faridho Awwal (Journal of Economics, Management, and Accounting, 2025)
This study examines the influence of Islamic financial literacy on the investment decisions of Indonesia’s millennial generation amid the growing relevance of ethical and sharia-based finance. Using a qualitative descriptive method through library research, the study analyzes theories, prior findings, and secondary data from OJK and academic sources. The results show that Islamic financial literacy positively shapes millennial awareness, attitudes, and confidence in making investment decisions, encouraging participation in Islamic investment products. However, literacy levels remain relatively low due to limited formal education, lack of engaging educational media, misconceptions about complexity, and low product accessibility. Barriers such as information asymmetry and minimal innovation still hinder broader adoption, though digital platforms and influencer engagement offer promising solutions. The study concludes that improving Islamic financial literacy requires collaboration between the government, industry, academics, and digital communities through education, innovation, and inclusive digital strategies. Enhancing millennial literacy will not only strengthen the Islamic finance sector but also support ethical and sustainable economic growth aligned with Islamic principles.